1999
DOI: 10.1046/j.1523-1747.1999.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

T Cells and T Cell-Derived Cytokines as Pathogenic Factors in the Nonallergic Form of Atopic Dermatitis

Abstract: A subgroup of patients with atopic dermatitis are known to have normal serum total immunoglobulin E levels, undetectable specific immunoglobulin E, and negative skin prick tests towards allergens. This form of the disease has been termed nonallergic atopic dermatitis. In this study, we found that, among 1151 chronic atopic dermatitis patients, about 10% had normal serum immunoglobulin E levels with no evidence for immunoglobulin E sensitization. We investigated immunologic mechanisms of patients with "allergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
179
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 169 publications
(193 citation statements)
references
References 51 publications
(63 reference statements)
10
179
1
3
Order By: Relevance
“…Acute lesions and early response after epidermal allergen application were characterized with a predominant type 2 cytokine pattern (4,16,57). Increased levels of IL-12 mRNA was demonstrated in chronic AD lesions (58), and chronic lesions were characterized by increased IFN-γ and decreased IL-4 levels, with more or less constant IL-5 and IL-13 levels (13,15,16,57,58). We observed killing of KCs by type 2 T cells after stimulation in the presence of IL-12.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Acute lesions and early response after epidermal allergen application were characterized with a predominant type 2 cytokine pattern (4,16,57). Increased levels of IL-12 mRNA was demonstrated in chronic AD lesions (58), and chronic lesions were characterized by increased IFN-γ and decreased IL-4 levels, with more or less constant IL-5 and IL-13 levels (13,15,16,57,58). We observed killing of KCs by type 2 T cells after stimulation in the presence of IL-12.…”
mentioning
confidence: 71%
“…T cells appear to be important players regulating inflammatory processes in eczematous dermatitis (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). This is supported by the observation that immunosuppressive drugs such as FK-506 and glucocorticoids, which block T-cell activation, are effective in treatment of eczematous disorders (4,5).…”
Section: Discussionmentioning
confidence: 98%
“…role in allergic eczema formation (29,31). Moreover, recent reports demonstrated that transgenic mice expressing caspase 1 in keratinocytes spontaneously developed AD-like skin disease with an elevation of the active form of IL-18 in serum (37).…”
Section: Discussionmentioning
confidence: 99%
“…Over 80% of patients with atopic dermatitis (AD) have increased IgEs to foods and inhalant allergens in the peripheral blood (43). However, the positive predictive value of IgE specific to food allergens is low (44).…”
Section: Food-specific T-cell Responses In the Skinmentioning
confidence: 99%